EFFECT OF SLANT CRACK ON WEAKENING MOTOR SHAFT STIFFNESS - JIN ZhiHao; ZHOU LingLing; YANG ZhengXin (Jixie qiangdu)
Based on fracture mechanics theory,the calculation formula of shaft with oblique crack under six loads,including axial force,moment and torque etc. along the main coordinate axis,was deduced at arbitrary inclination angles. The relationships between the stiffness and some parameters,including the crack inclination,the crack depth and the slenderness ratio etc. were discussed in a static and fully open crack. The calculation results show that the stiffness of the slant crack is increased with the decrease of crack inclination; And the stiffness of the oblique crack increases with the increase of the slenderness ratio; When the crack depth is small,the stiffness is changed slowly,But when the crack depth is greater than half the shaft radius,the impact of full loads should be considered,Meanwhile partial crack coupling stiffness is calculated,and coupling vibration affects the rotor’s dynamic performance.